Investigation of tribological properties of hexagonal boron nitride reinforced AZ91 magnesium composites produced by powder metallurgy - Macit, Cevher Kürşat; Gürgenç, Turan; Albayrak, Muhammet Gökhan; Özel, Cihan (Turkish Energy Nuclear and Mining Research Institute, 2023)
In this study, homogeneous composite materials were produced by supplementing AZ91 magnesium alloy and AZ91 alloy with 10% by weight hexagonal boron nitride (hBN) nanoparticles. The prepared powders were pressed by cold pressing method with 400 MPa pressure and sintered at 590°C in argon atmosphere. Microstructures of the samples were investigated by scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) analysis. The hardness values of the samples were taken from 5 different points during the 20 second loading time and the average hardness values were determined by taking the average of these hardness values. Wear tests were carried out in a pin-on-disc test device at different load values (5 N, 10 N and 15 N) at a total sliding distance of 300 m, at a sliding speed of 50 mm/sec and in dry conditions. The friction coefficient values and the weight losses as a result of wear were examined. The hardness value of AZ91 composite was 62 HB, while it was measured as 93 HB with hBN reinforcement. Similarly, in the wear tests, a composite with 10 times higher wear resistance was obtained with hBN additive. In summary, it has been observed that hBN additive has the potential to positively affect the mechanical and tribological properties of metal matrix materials. © 2023, Turkish Energy Nuclear and Mining Research Institute. All rights reserved.
Toz metalurijisi ile üretilen hegzagonal bor nitrür takviyeli AZ91 magnezyum kompozitlerin tribolojik özelliklerinin incelenmesi
Keywords: AZ91 Magnesium alloy; Hexagonal boron nitride; Microstructure; Powder metallurgy; Wear